CONSUMER PREFERENCE TOWARDS ORGANIC VEGETABLES IN SLEMAN DISTRICT - Nanda, Lintia Putri; Dewati, Rosita (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Public awareness of the importance of a healthy lifestyle and environmental conservation has increased in recent decades. Organic vegetables have their own advantages compared to conventional vegetables. The process of cultivating organic vegetables is free from the use of synthetic specifications and chemical fertilizers. Sleman Regency is one of the areas that has great potential in the development of organic products, especially vegetables. Supportive geographical conditions, many local farmers and high public awareness of the product make Sleman a relevant location for this study. Consumer preferences for organic vegetables are influenced by various factors in forming perceptions and purchasing decisions. This study uses conjoint analysis to determine consumer preferences for organic vegetables in Sleman Regency, as well as the combination of attributes preferred by consumers. The results of the analysis show that the order of attributes considered important in influencing the decision to purchase organic vegetables is 1) freshness, 2) price, 3) packaging and 4) label. The price attribute is the attribute that consumers consider most when purchasing organic vegetables. The combination of attributes preferred by consumers is organic vegetables with packaging, fresh (picked 1-2 days), with labels and with prices <10,000.